Ekman Transport as the Driver of Extreme Interannual Formation Rates of Eighteen Degree Water - Li, Ke; Maze, Guillaume; Mercier, Herlé (Journal of Geophysical Research: Oceans, 2022)
International audience In the North Atlantic subtropical gyre, the Eighteen Degree Water (EDW) is a voluminous heat reservoir, submerged under a seasonal pycnocline that can be progressively removed through the winter, allowing EDW ventilation in the early spring. We target the EDW formation extremes, namely 2004-2005, 2009-2010, and 2012-2013 for the strong years, and 2007-2008, 2008-2009, 2011-2012, and 2013-2014 for the weak years. We employ gridded hydrographic datasets mainly measured by Argo floats over the last 20 years, and provide a synthetic study on the extreme events of strong and weak EDW formation of this time period. We found that the Ekman transport is the indicator and driving mechanism explaining these extremes. Strong (Weak) EDW formation years correspond with atmospheric patterns resembling NAO- (NAO+), attributed to a strong (weak) winter air-sea surface heat loss, and a strong (weak) winter heat loss due to Ekman transport. Further, we show that such extreme Ekman advection patterns can be linked to mid-latitude storms, of which both intensity and duration have an impact on the extreme of EDW ventilation in the western subtropical North Atlantic. To yield a strong EDW formation, it requires a large winter heat deficit due to Ekman divergence, which can be sufficiently represented by numbers of strong winter storms, most notably, remnants of hurricanes and US east coast snowstorms. Meanwhile, to yield a weak EDW formation, apart from weak atmospheric forcings, a remnant positive heat content anomaly carried through from previous years would serve as an unfavorable preconditioning, hindering the EDW formation.